The role of explicit instruction in acquisition of English syllable structure among Ghanaians - Mohammed Sadat (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
The debate between effectiveness of explicit and implicit teaching has taken a center stage in the second language acquisition literature over a long period of time. Most of such debates center on grammar teaching and very few discuss suprasegmental features especially, syllable structure. All languages have some sort of syllabicity; however, the phonetic characteristics of syllables differ across languages. The difference can be seen in onset and coda. The current study examines the effects of explicit instruction on the acquisition of English syllable structure among Ghanaian learners of English. The paper investigates the efficiency of interventions through explicit teaching on the English syllable structure in a classroom setting. English syllables have some structures that are absent in the first language of the participants and these structures pose difficulties for speakers who learn English. This paper explores those structures and adopts explicit instruction as an intervention to remedy the difficulties. The investigation is done on participants who are Ghanaian speakers learning English. The study discovers that in disyllabic words there is a preference of trochaic syllables over iambic syllables, the acquisition of onsets is easier than acquisition of codas and finally, explicit teaching is very effective in the classroom.